Effect of fluoxetine or adenosine receptor NECA agonist on G-proteins of C6 glioma cells or NK immunocytes - Kovárů, Hana; Kovaru, Frantisek; Ondráčkova, Petra; Lisá, Vĕra; Fiserová, Anna (Neuro endocrinology letters, 2011)
OBJECTIVE: Neurochemical approaches to antidepressant effects and depressive disorder are also focusing on G-protein coupled receptors (GPCR) and subsequent signalling. Trimeric G-proteins play a crucial role in transmembrane signalling, its amplification and processing. It is evident that immune system participates in antidepressant mode of action by neurotransmitter GPCR. METHODS: We studied the effect of acute administration of fluoxetine or NECA agonist of adenosine receptor (GPCR) on C6 glioma cells and natural killer (NK) cell line, innate immunity. We used immunochemical estimation (ELISA) of the main types of G-protein alpha subunits from isolated membranes of tested cells. RESULTS: Significant reduction of G alpha q/11 subunits after acute administration of fluoxetine or NECA agonist was found. In contrast, no significant influence of G alpha s or G alpha i1,2 subunit levels of C6 glioma cells were observed. Lowered Gq/11 signalling was in accordance with decreased 2nd messenger 1,4,5 IP3 formation by PLC. Acute effect of fluoxetine or NECA agonist on NK cell line resulted in significantly reduced G alpha q/11 levels without changes in G alpha s and G alpha i1,2. Furthermore, we determined that NECA agonist was able to abolish fluoxetine-evoked G alpha q/11 levels of NK cell line. CONCLUSIONS: Results show involvement of fluoxetine in the C6 glioma signal transduction and were comparable with NK cells. Similar inhibiton of G alpha q/11 by NECA agonist in both C6 glioma cells and NK cell line was determined. Furthermore NECA induced attenuation of fluoxetine evoked Galpha q/11 signalling can indicate parallel interference between GPCR and final response. Finally, we determined similarity in both interleukin 2, IL2 immunostimulator and fluoxetine evoked G q/11 levels in NK cell line and thus fluoxetine action could be related to signalling aspects of neuroimmunomodulatory activity.
Keywords: imipramin; Animals; Antidepressive Agents, Tricyclic; Enzyme-Linked Immunosorbent Assay; gliom; Selective Serotonin Reuptake Inhibitors; Cell Line, Tumor; fluoxetin; interleukin-2; buňky NK; Fluoxetine; proteiny vázající GTP; imunologické faktory; Rats, Inbred F344; nádory mozku; lidé; GTP-Binding Proteins; Interleukin-2; signální transdukce; Glioma; Imipramine; Signal Transduction; Adenosine-5'-(N-ethylcarboxamide); adenosin-5'-(N-ethylkarboxamid); selektivní inhibitory zpětného vychytávání serotoninu; ELISA; Immunologic Factors; Killer Cells, Natural; Brain Neoplasms; potkani inbrední F344; krysa rodu Rattus; zvířata; Rats; Serotonin Uptake Inhibitors; nádorové buněčné linie; antidepresiva tricyklická; Humans